Economic Decentralization through Blockchain Opportunities Challenges and New Business Models - Berlilana; Arif Mu’amar (Bright Institute, 2024)
Blockchain technology has emerged as a transformative force with the potential to decentralize economic systems and create innovative business models. This paper explores the opportunities and challenges associated with economic decentralization through blockchain, focusing on the development and sustainability of new business models such as Decentralized Finance (DeFi) platforms and Decentralized Autonomous Organizations (DAOs). The study employs a qualitative research design, incorporating a comprehensive literature review and detailed case studies of prominent blockchain-based platforms. The findings highlight the significant potential of blockchain to democratize access to financial services, enhance transparency, and reduce reliance on intermediaries. However, the study also identifies critical challenges that must be addressed for blockchain to achieve widespread adoption. These include scalability issues, regulatory uncertainty, and security vulnerabilities, all of which pose significant risks to the sustainability of blockchain-based business models. A SWOT analysis is conducted to provide a structured evaluation of these strengths, weaknesses, opportunities, and threats, offering insights into the strategic position of blockchain in various industries. The analysis reveals that while the opportunities for innovation and disruption are vast, the path to realizing these benefits is fraught with technical, legal, and operational challenges. The paper concludes that ongoing research, technological advancements, and regulatory clarity will be essential to unlocking the full potential of blockchain technology in driving economic decentralization.